Silica from Natural Sources: a Review on the Extraction and Potential Application as a Supporting Photocatalytic Material for Antibacterial Activity - Annisa Luthfiah; Yusi Deawati; M. Lutfi Firdaus; Iman Rahayu; Diana Rakhmawaty Eddy (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Silica has become a popular material due to its high abundance and many advantages in various fields. This material can be produced synthetically and extracted from nature with resultant advantages in the application of green production. Therefore, this article deals with the form of silica extracted from quartz sand, leaves, and agricultural wastes found in nature. The extraction process from various sources would be described using thermal, biological, and chemical methods. This review also highlights the potential application of silica as a photo catalytic antibacterial-supporting material and discusses its role in increasing the effectiveness of the process. The discussion was continued with research on this procedure, where synthetic auxiliary materials were compared to the extracted silica. Furthermore, results obtained indicated that the extracted material had very good potential as a photocatalyst adjunct in its application in the antibacterial field.